Servidumbre y literatura: entre apocalipsis y revelación (Altre Modernità, 2013)
The article describes the figure of the “sirvienta” in 5 contemporary Latin American authors and correlates it with a newspaper article recently appeared. The article tries to show how reality and literature represent a situation of semi-slavery in modern times.